Methods of business processes competitiveness increasing of the rocket and space industry enterprise. Issue 4 (May 2019) - Kukartsev, A V; Boyko, A A; Kukartsev, V V; Tynchenko, V S; Bukhtoyarov, V V; Tynchenko, S V
Abstract: This article observes problems of the branches of the Russian defense industry complex. The short comparative analysis of scientific approaches and applied methods of management of innovative business processes of the enterprise of the rocket and space industry is carried out. Features and area of assignment of a system method of management and enhancement of innovative business processes of the enterprise and the method based on "end-to-end" business processes are provided. Need of transition from functional approach to enterprise management, widespread in the last century, to process-based management is proved. The algorithm for increasing the competitiveness of business processes of an enterprise of rocket and space industry is considered in the article. It allows to consider the nature and conditions of implementation of innovative activities and provide not only the effective use of limited resources, but also the sustainable development of the rocket and space industry enterprise and an industry in general, allowing to successfully solve problems of increase in defense capability of the state. The need of control technique development by innovative business processes of the rocket and space industry enterprise, necessary for increase in their competitiveness, is proved.